E-learning as a Tool in Spreading Knowledge in Organization Management - Polakovič, Peter; Hallová, Marcela; Cichoń, Magdalena (Zeszyty Naukowe Wyższej Szkoły Bankowej w Poznaniu, 2018)
Thanks to e-learning employees of an organization learn what they need at a given moment, what they need to learn in a specific place and time, at their own pace and in their preferred way. E-learning provides the standardization of knowledge, facilitates contact with the environment, makes training convenient, provides conceptuality, multithreading and individualization of training, and is an interactive and engaging form of training. E-learning is a tool that should be more widely used in the future in the dissemination of knowledge, including in the field of finance and accounting, and its effective use requires a wider integration of international experts in the development of training programs and workshops. The aim of the article is to discuss e-learning as a tool for management, characterizing the system of learning management and effective management of information technologies in organizations, including public ones.(original abstract)